Women’s expectations regardings medical outpatient implemented in gynaecological - Rycerz-Genca, Justyna; Węgorowski, Paweł; Michalik, Joanna; Domżał-Drzewicka, Renata; Stanisławek, Andrzej (Journal of Education, Health and Sport, 2018)
Admission Primary health care is the first level of a professional medical service, to which patients with their ailments and health problems apply. Access to basic health care services should be free from any physical, organizational and financial barriers due to the willingness to use the services of various patients. Objective of the work The aim of the work was to get to know the expectations of women regarding the medical care provided in the gynaecological clinic. In order to achieve the research objective, the issues concerning, among other things, the level of satisfaction of women with the functioning and offering of medical services in the gynecological clinic as well as the expectations of women during visits to the gynecological clinic were chosen. Material and methods The research was based on the method of a diagnostic survey using a standardized questionnaire, which was addressed to women using gynecological outpatient services. Results The research shows that the most frequent respondents visited the gynecologist once every three years, (49.33%, n = 74). Statistical analysis showed a significant relationship between the professional activity of the surveyed women and the frequency of visits to the gynecologist (p = 0.004). The study showed that most often during the visit to the gynecological clinic, the respondents expected: gynecological examination (93.33%), cytological examination (83.33%) and breast examination (69.33%). Conclusions Expectations of women during a visit to the gynecological clinic concern primarily the obtaining of information on research and treatment. Women using the gynecological clinic are satisfied with the offered medical services and the way the clinic operates. Women aged 30-41 with higher education are significantly more satisfied with the gynecological clinic than women under 30 and over 40 years of age and with basic or vocational and married education.